Triazole‐Pyridine Dicarbonitrile Targets Phosphodiesterase 4 to Induce Cytotoxicity in Lung Carcinoma Cells. Issue 9 (29th August 2019) - Keerthy, Hosadurga K.; Mohan, Surender; Basappa,; Bharathkumar, Hanumantharayappa; Rangappa, Shobith; Svensson, Fredrick; Bender, Andreas; Mohan, Chakrabhavi Dhananjaya; Rangappa, Kanchugarakoppal S.; Bhatnagar, Rakesh
Abstract: Phosphodiesterase 4 (PDE4) is a key enzyme involved in the hydrolysis of cyclic adenosine monophosphate (cAMP) and widely expressed in several types of cancers. The inhibition of PDE4 results in an increased concentration of intracellular cAMP levels that imparts the anti‐inflammatory response in the target cells. In the present report, two series of triazolo‐pyridine dicarbonitriles and substituted dihydropyridine dicarbonitriles were synthesized using green protocol (TBAB in refluxed water). We next evaluated the title compounds for their cytotoxicity towards lung cancer (A549) cells and identified 7′‐[4‐(methylsulfonyl)phenyl]‐5′‐oxo‐1′, 5′‐dihydrospiro[cyclohexane‐1, 2′‐[1, 2, 4]triazolo[1, 5‐ a ]pyridine]‐6′, 8′‐dicarbonitrile (5h ) and 7′‐(1‐methyl‐1 H ‐imidazol‐2‐yl)‐5′‐oxo‐1′, 5′‐dihydrospiro[cyclohexane‐1, 2′‐[1, 2, 4]triazolo[1, 5‐ a ]pyridine]‐6′, 8′‐dicarbonitrile (5j ) as lead analogs with the IC50 values of 15.2 and 24.1 μm, respectively. Furthermore, all the new compounds were tested for PDE4 inhibitory activity and 5j showed relatively good inhibitory activity towards PDE4 with inhibition of 50.9 % at 10 μm . In silico analysis demonstrated the favorable interaction of the title compounds with the target enzyme. Taken together, the present study introduces a new scaffold for the development of novel PDE4 inhibitors to fight against inflammatory diseases. Abstract :